Translation techniques for similar plural nouns in the Qur’an - Hana Siti Hapsah; Maman Abdurahman; Nalahuddin Saleh (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2026)
The translation of similar plural nouns in Qur’an presents a challenge for translators, as such forms may carry different meanings and contextual nuances across verses. Therefore, translators commonly employ various translation techniques to assist in determining the most appropriate equivalents during the translation process.  This study examines the application of translation techniques and the resulting shifts found in the rendering of similar plural nouns in two Indonesian translations of the Qur'an, the KFGQPC translation and the Kemenag RI 2019 translation. The focus of this research is to describe how translation techniques are applied and to identify translation shifts in similar plural nouns across these two versions. A qualitative descriptive method was employed. The data were collected purposively based on specific criteria, namely verses containing plural nouns derived from the same singular form and showing differences in how they are rendered in the two Indonesian translations. As a result, the sample is inherently limited to forms that meet these criteria. The findings indicate that amplification and literal translation are the most frequently employed techniques. The prominence of amplification relates to the implicit meanings embedded in several plural forms, which require explicitation, whereas literal translation is chosen when the equivalent can be transferred directly without any loss of meaning. Other techniques appear only occasionally, as the linguistic nature of the selected plural nouns seldom demands additional adjustments such as borrowing, modulation, or particularization. The shifts identified in the translations include a formal shift at the morphemic level, arising when plural forms in the source language are rendered as singular forms in the target language, and meaning shifts involving movements between generic and specific meanings, which occur when contextual meaning must be adjusted to ensure greater accuracy in the target language.